The Effectiveness of the Talking Pen Al-Qur'an Audio Visual Media in Improving the Ability to Read the 5 Makharijul Huruf (Experimental Study) - Mutiara Raja; Mustafa Mustafa; Nurhidayanti Nurhidayanti (Educational Journal of Learning Technology, 2026)
This study examines the use of the audiovisual Talking Pen Al-Qur'an media for learning the five Makharijul Huruf. The objectives are: (1) to determine students' understanding of reading the Qur'an after using the media, and (2) to determine their reading ability. This experimental study employed a one-group pretest-posttest design with 24 students (8 males, 16 females). Instruments included tests of understanding and reading ability, while data collection used tests, observation, and documentation. Data were analyzed using descriptive statistics. Results showed: (1) The average pretest score for understanding was 32.54 (very poor), which increased to 83.83 (good) after intervention. (2) The average pretest score for reading ability was 49.54 (poor), which increased to 80.54 (good) after intervention. Thus, the audiovisual Talking Pen Al-Qur'an media significantly improves both understanding and reading ability in Makharijul Huruf.